2019
DOI: 10.1111/pai.13120
|View full text |Cite
|
Sign up to set email alerts
|

Measurement properties of quality‐of‐life outcome measures for children and adults with eczema: An updated systematic review

Abstract: ObjectiveThe aim of this updated systematic review was to systematically assess the measurement properties of previously discussed and new quality‐of‐life patient‐reported outcome measures (PROMs) in children and adults with eczema using the new COSMIN guideline.MethodsA systematic literature search was conducted in PubMed and EMBASE. Eligible studies reported on measurement properties of quality‐of‐life PROMs for children and adults with eczema. The methodological quality of selected already known PROMs and n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 49 publications
2
36
0
Order By: Relevance
“…As in other disease areas such as atopic dermatitis and psoriasis, identifying the most appropriate patient-reported outcome instruments is important to ensure standardization in clinical trials and to establish standards of care in clinical practice for patients with CTCL. [21][22][23][24] Additionally, this study highlights the need for integration of mental health services into the multidisciplinary care of patients with CTCL in order to better address issues of self-image, social isolation and psychological distress.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…As in other disease areas such as atopic dermatitis and psoriasis, identifying the most appropriate patient-reported outcome instruments is important to ensure standardization in clinical trials and to establish standards of care in clinical practice for patients with CTCL. [21][22][23][24] Additionally, this study highlights the need for integration of mental health services into the multidisciplinary care of patients with CTCL in order to better address issues of self-image, social isolation and psychological distress.…”
Section: Discussionmentioning
confidence: 92%
“…Moving forward, incorporating these findings that distinguish patients with CTCL from other patient populations will be paramount in developing a comprehensive disease‐specific instrument that adequately captures their illness experience. As in other disease areas such as atopic dermatitis and psoriasis, identifying the most appropriate patient‐reported outcome instruments is important to ensure standardization in clinical trials and to establish standards of care in clinical practice for patients with CTCL 21–24 …”
Section: Discussionmentioning
confidence: 99%
“…Even the DLQI has several serious issues, e.g. double‐barrelled and redundant items and evidence for insufficient measurement properties 31,32 . In this study, data were collected across multiple countries using different language versions of the HidroQoL.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials have shown that a reduction in AD severity correlates well with improvement in quality-of-life scores and decrease in anxiety and depression scores, in turn, indicating that these symptoms are reversible. 34,35 However, unfortunately, the quality-of-life outcomes typically used tend to be insufficiently sensitive to change, 36,37 making it difficult to measure the true effect of AD treatment on the psychiatric symptoms.…”
Section: Discussionmentioning
confidence: 99%